The solo broadcast journalism practices from an industry perspective - Awan Ismail; Aselawati Che Ab Adziz; Rizalawati Ismail; Faridah Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social networking is a rapidly growing source of news in broadcast journalism. Broadcast journalism is facing a continuing decline in electronic media circulation and social media changes. The concept of online convergence in broadcast journalism has become a news trend on social media. Solo broadcast journalism and social media are becoming practices in news organisations today. Therefore, this article aims to identify the practices of solo broadcast journalism from an industry practitioner’s perspective. A qualitative methodological approach was used in this study. Face-to-face interviews were conducted with eight informants who practised solo broadcast journalism. The data were analysed thematically. The results showed that production tasks, location reviews, good time management, relationships with the community, preparation tasks, and comfortable places are among the concepts of practising solo broadcast journalism in news organisations. The findings of this study show that journalists practice solo broadcast journalism to get news in line with the development of digital media today. The findings of this study are expected to benefit the National ICT Agenda on National Broadband Policy from the perspective of newspaper organisations in expanding the use of technology in the distribution and publication of stories for news. The findings of this study will help make appropriate adjustments to develop human capital by integrating broadcast journalism practices with technology-assisted work in solo broadcast journalism. In addition, this study is also significant to the National Education Policy. The study will impact the educational curriculum of broadcast journalism by introducing changes in line with the development of solo broadcast journalism.